Implementation of Modified Curriculum at Elementary School Muhammadiyah 2 Sidoarjo - Syafi', Moh. Agus Syairofi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to examine the implementation of the Modified Curriculum at SD Muhammadiyah 2 Sidoarjo. A qualitative descriptive approach was used, with data collected through interviews, observations, and documentation. The findings reveal that lesson planning, implementation, evaluation, and the challenges encountered are integral components of the curriculum implementation process. In the planning phase, an initial needs assessment is conducted, followed by the development of a syllabus that includes setting learning objectives and preparing self-instructional modules. During the implementation phase, learning activities are carried out in three stages: introductory, core, and closing, with differentiated classes. In the evaluation phase, students receive support through enrichment programs, counseling, or assignments either individually or in groups. The requirement to develop self-instructional modules in a very short time places a significant burden on teachers.